Projeto de Monitoramento de Praias (PMP): potencialidades e limites para a conservação costeira e marinha - Dias, Renata Balsamo (2018)
Among the environmental programs implemented in regions potentially impacted by oil activity is the Beach Monitoring Program (PMP). Its objective is to evaluate the possible impacts caused by the exploration, production and out flow of oil and gas in marine tetrapods (birds, turtles and mammals), through stranding monitoring, rescue and rehabilitation of these animals. The objective of the research was to study the Beach Monitoring Project as a subsidy in coastal management, with emphasis on areas where there are Protected Areas (PAs). Therefore, the research was based on two case studies: the Beach Monitoring Program of the Campos and Espírito Santo basins (PMP BC-ES) which occurs on the northern coast of Espírito Santo and the Beach Monitoring Program of Santos Basin phase 1 (PMP-BS Fase 1), on the southern coast of the state of São Paulo, both are held due to the activities of PETROBRAS. Documentary research and semi-structured interviews were carried out, with the purpose of knowing the implementation, planning and execution of PMPs, as well as raising the involvement of the main social actors in this process. The main results obtained were the contributions in knowledge about the coastal and marine environment generated by the PMP data, as well as the impacts of human activities in this environment. In addition, direct and indirect contributions were made to the use of PMP data in the planning and management of PAs, such as assistance in the monitoring of the territory due to the daily activities of the field teams, technical basis for the creation of new PAs and use of data to integrate the Management Plans. However, for such contributions to occur issues related to data accessibility failures should be addressed and participation of society in general, as well as the different actors involved in the management of these areas, should be encouraged.